Proton pump inhibitors - possible side effects of long-term therapy: a review - Jan Kowalewski; Damian Bęben; Grzegorz Pyc; Łukasz Kowalewski (Quality in Sport)
Introduction and purpose: Proton pump inhibitors (PPIs), which have been on the market for more than 30 years, are widely regarded as safe and effective medications. For this reason, they are very popular with both doctors and patients. PPIs find their use in the treatment of such ailments as gastroesophageal reflux, gastric ulcer disease or as a shielding therapy when taking non-steroidal anti-inflammatory drugs. Nevertheless, their long-term use may be associated with many side effects. The purpose of our review is to summarize the knowledge in the current medical literature on the possible complications of chronic use of PPIs.